205k views
0 votes
Help help help help help

Help help help help help-example-1

1 Answer

6 votes

Answer:

Option 2:
f^((-1))(x) = -(3)/(4x) is the correct answer.

Explanation:

Given function is:


f(x) = -(3)/(4x)

There are few steps to find inverse of a function. We will apply them one by one onto the function

Step 1: Replacing f(x) with y


y = -(3)/(4x)

Step 2: Replacing y with x and x with y


x = -(3)/(4y)

Step 3: Solving the equation in step 2 for y


x = -(3)/(4y)\\y = -(3)/(4x)

Step 4: Replacing y with inverse of f


f^((-1))(x) = -(3)/(4x)

Hence,

Option 2:
f^((-1))(x) = -(3)/(4x) is the correct answer.

User Secto Kia
by
5.2k points